Characterization and immune function of the interferon-β promoter stimulator-1 in the barbel chub, Squaliobarbus curriculus. (March 2020) - Zhao, Xin; Xiao, Tiaoyi; Jin, Shengzhen; Wang, Jing'an; Wang, Junya; Luo, Hong; Li, Rui; Sun, Tong; Zou, Jun; Li, Yaoguo
Abstract: To elucidate the immunity-protecting role of the interferon-β promoter stimulator-1 (ScIPS-1) in barbel chub Squaliobarbus curriculus, the full-length cDNA of ScIPS-1 was cloned and expression levels in response to stimulation were investigated. In addition, the function of ScIPS-1 and its domains were analyzed. The full-length cDNA of ScIPS-1 is 2524 bp and encodes 601 aa. The N-terminal caspase activation and recruitment domain, central proline-rich domain, C-terminal transmembrane domain, C2 HC-zinc finger, and Cwf21 domains were identified. The mRNA level of ScIPS-1 was the highest in the kidney, whereas the highest protein level was observed in the liver. The ScIPS-1 expressions were significantly up-regulated after lipopolysaccharide and poly I:C treatment. The ScIPS-1 protein level was up-regulated at 12 h in the head kidney and was up-regulated at 12 h and then down-regulated from 12 to 48 h in the liver after grass carp reovirus (GCRV) infection. The CiIFN and CiMx transcription levels were significantly enhanced in pEGFP-C1-IPS-1 and pcDNA3.1-ΔCwf21 overexpressing cells after GCRV infection. The results indicate that ScIPS-1 may function in the immune response against pathogens and provide a basis for achieving resistance to diseases in fish breeding. Highlights: A 2524 bp full-length IPS-1 cDNA was cloned from the barbel chub. ScIPS-1 mRNA levels were up-regulated after LPS and Poly I:C treatment. pEGFP-C1-IPS-1 overexpressing activated IPS-1, CiIFN and CiMx transcription. Deletion of cwf21 domain in ScIPS-1 resulted in up-regulation of CiIFN and CiMx.